1994
DOI: 10.1104/pp.106.2.661
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Acclimation in Pea and Soybean to High Atmospheric CO2 Partial Pressure

Abstract: Nonnodulated pea (Pisum safivum 1. cv Frosty) and soybean (C/ycine max [L.] Merr. cv Wye) plants were grown under artificial lights from germination with ample nutrients, 600 pmol photons m-2 s-', and either 34 to 36 (control) or 64 to 68 Pa (enriched) CO,. For soybean, pod removal and whole-plant shading treatments were used to alter the source-sink balance and carbohydrate status of the plants. Crowth of both species was substantially increased by CO, enrichment despite some down-regulation of photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 11 publications
4
51
2
Order By: Relevance
“…In addition, Sage et al (1989) found that the deactivated Rubisco immediately after exposure to elevated CO, levels does not recover during the subsequent prolonged exposure, and they pointed out that this indicates an incomplete acclimation to elevated CO, levels. On the other hand, there have been some reports that the activation state of Rubisco at elevated CO, partial pressures is unchanged in soybean (Campbell et al, 1988;Sicher et al, 1995), loblolly pine (Tissue et al, 1993), tobacco (Sicher and Kremer, 1994), and pea (Xu et al, 1994). In rice Rowland-Bamford et al (1991) observed that Rubisco activation declined in the plants grown at 90 Pa CO,, whereas it was not affected in the plants grown at CO, levels up to 60 Pa.…”
Section: Rubisco Activation At Elevated Comentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Sage et al (1989) found that the deactivated Rubisco immediately after exposure to elevated CO, levels does not recover during the subsequent prolonged exposure, and they pointed out that this indicates an incomplete acclimation to elevated CO, levels. On the other hand, there have been some reports that the activation state of Rubisco at elevated CO, partial pressures is unchanged in soybean (Campbell et al, 1988;Sicher et al, 1995), loblolly pine (Tissue et al, 1993), tobacco (Sicher and Kremer, 1994), and pea (Xu et al, 1994). In rice Rowland-Bamford et al (1991) observed that Rubisco activation declined in the plants grown at 90 Pa CO,, whereas it was not affected in the plants grown at CO, levels up to 60 Pa.…”
Section: Rubisco Activation At Elevated Comentioning
confidence: 99%
“…Growth under high CO, partial pressures leads to carbohydrate accumulation. Since an apparent correlation between carbohydrate accumulation and the suppression of photosynthesis has often been reported (Sasek et al, 1985;Peet et al, 1986;Yelle et al, 1989;Wong, 1990;Xu et al, 1994), much attention has been paid to the causal relationship(s) between the two phenomena. Stitt (1991) proposed the existence of a feedback mechanism(s) by which the accumulation of carbohydrate indirectly leads to a decrease in the amounts of key components of the photosynthetic apparatus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Total soluble protein and Rubisco contents (g m -2 ) have been observed to decline in response to CO 2 enrichment in D. richardsonii (Lutze & Gifford, unpublished). Rubisco (Sage, Sharkey & Seemann 1989;Besford 1990;RowlandBamford et al 1991) and chlorophyll contents (g m -2 ; Sage et al 1989;Xu, Gifford & Chow 1994) have often decreased in a range of plant species in response to CO 2 enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence from high CO 2 treatment experiments using various C 3 plants that decreased Rubisco activity in leaf rather than changes in leaf Rubisco content is likely to be a main cause (Sage et al, 1989). Data from experiments conducting excisions of sink organs (pods or flower buds and flowers) or petiole girdling suggest that a decrease of stomatal conductance or Rubisco activity or Rubisco content in leaf, or both decreases of Rubisco activity and Rubisco content in leaf can be responsible for the decrease in leaf photosynthetic rate under excessive photosynthetic source capacity (Mondal et al, 1978;Wittenbach, 1982Wittenbach, , 1983Xu et al, 1994;Crafts-Brandner & Egli, 1987;Cheng et al, 2008). As described in the Introduction, excising sink organs or high CO 2 treatment can have side effect(s) other than inducing excessive photosynthetic source capacity.…”
Section: Discussionmentioning
confidence: 99%